The Elasticity of Interest Rate Volatility: Chan, Karolyi, Longstaff, and Sanders Revisited - Robert R. Bliss; David C. Smith (Federal Reserve Bank of Atlanta, 1997)
This paper presents a careful reexamination of Chan, Karolyi, Longstaff, and Sanders (CKLS 1992). By redefining the possible regime shift period in line with evidence from known policy changes and past empirical research, we find evidence that contradicts the major results in their paper. The widely cited conclusion of their paper is that the elasticity of interest rate volatility is 1.5. CKLS also concluded that there was no structural shift in the interest rate process after October 1979. When the structural shift period is defined to be temporary and coincident with the Federal Reserve Experiment of October 1979 through September 1982, we find that there is strong evidence of a structural break. Furthermore, we find evidence that, contrary to CKLS's claim, a moderately elastic interest rate process can capture the dependence of volatility on the level of interest rates, while highly elastic models cannot. In particular, this study finds support for the square-root CIR process. These results are robust to changes in the short-rate data used and the treatment of outliers.
Keywords: 330; Econometric models; Interest rates; Money